Fuqaha's Views On Siri Marriage - Adrianto Adrianto; Khalid Sitorus; Diana Farid; Baktybek Patronimik; Sofia Gussevi (Universitas Muhammadiyah Bandung, 2025)
Marriage is a sacred institution that is safeguarded by Sharia to ensure fairness, openness and sustainability of the relationship between husband and wife. One of these safeguards is the presence of guardians and witnesses in the marriage contract. Hikmah at-Tasyri' shows that the presence of guardians and witnesses serves as a deterrent to fraud and as a form of strengthening the marriage bond. In fact, the Prophet Muhammad SAW recommended announcing the marriage through a celebration or walimah. This research uses a qualitative approach with a library research method, which examines the opinions of classical and contemporary scholars regarding the importance of the presence of witnesses and publication in marriage. The results show that marriage that is not witnessed, not publicized, and not registered is not permissible. As for marriages that are witnessed by two witnesses but the witnesses have been “ordered” or are not independent, it is ruled makruh by several companions and tabi'in such as Umar RA, Urwah, Abdullah ibn Ubaidillah, Ibn Utbah, Sa'bi, Nafi' (servant of Ibn Umar), as well as imams such as Abu Hanifah, Shafi'i, and Ibn Munzir. Thus, it can be concluded that the presence of witnesses and publication in marriage is a sunnah muakkadah that is highly recommended to maintain the transparency and legality of marriage in the view of sharia.